Development of Instant Porridge Complementary Feeding with Catfish Flour and Pumpkin Flour Substitution: Pengembangan Makanan Pendamping Air Susu Ibu (MP-ASI) Bubur Instant dengan Substitusi Tepung Ikan Lele dan Tepung Labu Kuning - Sri Darningsih; Nur Ahmad Habibi Habibi; Zurni Nurman; Ismanilda Ismanilda (Media Gizi Indonesia, 2023)
The problem of malnutrition in infants and toddlers led to growth and development impairment. In the long term, nutritional problems increased the risk of disease and lower productivity. A method to overcome malnutrition was by using complementary feeding. This study aimed to create and evaluate the quality, safety and shelf life of instant porridge complementary feeding with the substitution of catfish flour and pumpkin flour. The method used in this study was an experimental study with two factorial completely randomized design with two repetitions to evaluate the product sensory. Furthermore, quality and safety testing was carried out according to the parameters set by Indonesia National Standard and Indonesia National Food and Drug Agency. In the final stage, the shelf life evaluation was carried out using the Extended Storage Studies (ESS) method using room temperature 27-37oC. The results showed that the use of catfish flour as much as 15% and pumpkin flour as much as 10% gave the best results on the sensory value of instant porridge. The product had a fairly good nutritional value, and safe in terms of heavy metals and microbiology. However, the water content of the product was still too high from the standard. The result of shelf life testing using the ESS method, instant porridge products had shelf life of 6 months at room temperature 27-37°C. The implications of this research can be used as a reference in the development of complementary feeding made from local food.